DNA BARCODING APPLICATION OF MITOCHONDRIAL COI GENE TO IDENTIFY SOME FISH SPECIES OF FAMILY GOBIIDAE IN VIETNAM - Linh, Nguyen Manh; Thu, Pham The; Quan, Nguyen Van; Chien, Pham Van; Ly, Dao Huong; Nhan, Dinh Van; Len, Dam Thi (Vietnam Journal of Marine Science and Technology, 2019)
The family Gobiidae is a relatively high abundance family of coastal fish with about 2000 species in 210 genera described. In Vietnam, the study on Gobiidae is very complex due to the large number of species, small size and high morphological variation which makes difficulties in identification and classification. In this study, the DNA barcoding technique has been used through mitochondrial cytochrome oxidase I (COI) gene to classify 30 specimens of Gobiidae from three coastal areas (North, Central and South) in Vietnam to evaluate the effectiveness compared to the morphological classification method. Results showed that 26 species belonging to 21 genera were determined by the COI barcode while 19 species (17 genera) were determined when using morphological method. Mahidolia mystacina was new recorded in Vietnam. The DNA barcodes of COI gene developed in this study could be useful for estimating phylogenetic diversity as well as other studies of gobiids in terms of conservation, management and utilization of fisheries resources in Vietnam. In addition, the results showed the high potentiality in using COI barcode to identify marine fish.